Vibration and Noise Analysis of 4Ф Switched Reluctance Motor Drive - Mekala N; Muniraj C; Ramesh Balaji S.M. (Institute of Advanced Engineering and Science, 2015)
The Switched Reluctance Motor (SRM) is getting large attention for industry application due to their simple construction, high starting capabilities, high reliability, and high efficiency and also rotor carries no windings, no slip-rings there is no brushes, it requires less maintenance. In spite of the merits, it had some demerits like acoustic noise and vibration is one of major issues in SRM. The DSP-TMS320F28335 processor were implemented due to their high performance for the control applications.In this work the Random Pulse Width Modulation (RPWM) technique is used to reduce the acoustic noise and vibration by varying random turn on and turn off angle control.The acoustic noise and vibration signals are measured using accelerometer and sound level meter in 1HP, 8/6poles of SRM drive. The experimental analysis of vibration signals are measured using Lab VIEW at different speeds and load conditions. The acoustic noise signals are measured using Sound level meter .Both the Acoustic and vibrations are analyzed experimentally for different speeds and load conditions. The experimental results show that the noise and vibration analysis and also compare the sinusoidal PWM is better than Random PWM techniques. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7965